2018
DOI: 10.1111/oik.05844
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal shifts in the importance of bottom–up and top–down factors on stream periphyton community structure

Abstract: We examined the importance of temporal variability in top–down and bottom–up effects on the accumulation of stream periphyton, which are complex associations of autotrophic and heterotrophic microorganisms. Periphyton contributes to primary production and nutrient cycling and serves as a food resource for herbivores (grazers). Periphyton growth is often limited by the availability of nitrogen and phosphorus, and biomass can be controlled by grazers. In this study we experimentally manipulated nutrients and gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 66 publications
(146 reference statements)
0
16
0
1
Order By: Relevance
“…A pesar de no presentar diferencias significativas a nivel espacial es importante mencionar que la localidad racv presentó la mayor densidad en la cuenca del río Alvarado. Esto se puede atribuir, principalmente, a la moderada velocidad del caudal (0,262 m 3 /s) [35], [36], y a la influencia de algunos parámetros fisicoquímicos, como, por ejemplo, coliformes totales [36] y fósforo [37], que favorecen el establecimiento y desarrollo de un gran número de organismos. Por otra parte, la baja densidad observada para la localidad qche se debe, probablemente, a la intervención antrópica, producto de la extracción mineral observada en campo durante los muestreos realizados, la cual influye drásticamente en el establecimiento de la comunidad fitoperifítica.…”
Section: Discussionunclassified
“…A pesar de no presentar diferencias significativas a nivel espacial es importante mencionar que la localidad racv presentó la mayor densidad en la cuenca del río Alvarado. Esto se puede atribuir, principalmente, a la moderada velocidad del caudal (0,262 m 3 /s) [35], [36], y a la influencia de algunos parámetros fisicoquímicos, como, por ejemplo, coliformes totales [36] y fósforo [37], que favorecen el establecimiento y desarrollo de un gran número de organismos. Por otra parte, la baja densidad observada para la localidad qche se debe, probablemente, a la intervención antrópica, producto de la extracción mineral observada en campo durante los muestreos realizados, la cual influye drásticamente en el establecimiento de la comunidad fitoperifítica.…”
Section: Discussionunclassified
“…Although the current study cannot clearly separate the effects of the electrical current from those that are associated with wading, we hypothesize that the effects of electrofishing activities on biofilms that were documented here are due primarily to wading in the stream. We hypothesize this because studies have used electricity in streams explicitly in research on aquatic biofilm to exclude grazers and thereby quantify top‐down control on benthic biofilms (Opsahl et al 2003; Lourenço‐Amorim et al 2014; Beck et al 2019). In those studies, electricity is not identified as a factor limiting primary production.…”
Section: Discussionmentioning
confidence: 99%
“…In one example, electrified tiles where grazers were excluded had biofilm standing stocks that were two to three times greater than those on control tiles, with the highest biofilm abundance occurring closest to the electrical wires (Opsahl et al 2003). Beck et al (2019) evaluated the potential effect of electrical fields on biofilms in their study and found some differential responses among a few taxa in the algal community but no significant overall effects of the electrical field on biofilm ash‐free dry mass.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the nutritional quality of periphyton may indirectly influence the strength of top‐down control. Grazer behavior is known to affect periphyton community structure through selective feeding and nutrient regeneration (Mulholland et al 1991, Rosemond et al 2000, Beck et al 2019); fluctuations in nutrient availability are likely to interact with top‐down control by affecting grazer behavior, as in, e.g., compensatory feeding (Iannino et al 2019). Future studies should focus on how long‐term bottom‐up effects would alter grazer growth and behavior, and how this would in turn influence periphyton biomass and nutritional quality.…”
Section: Discussionmentioning
confidence: 99%